Optimizing renewable energy potential in island areas based on analytical hierarchy process - Hasibuan, Arnawan; Sayuti, Muhammad; Siregar, Widyana Verawaty; Hidayatullah, Ferdy; Daud, Muhammad; Azmi, Azmi; Azman, Azman; Almunadiansyah, Rizky; Roid, Fahrian (Institute of Advanced Engineering and Science, 2025)
The decreasing availability of fossil fuels and their contribution to environmental degradation and emissions of harmful gases has encouraged a shift to renewable energy sources. This change aims to produce electricity without using fossil fuels. Banyak Islands, a new tourist destination in Aceh Singkil, Indonesia, is experiencing an increase in visitors, increasing electricity demand currently supplied by diesel power plants. Therefore, this research aims to examine the possibilities of wind and solar power plants and assess their energy output. The four factors used to determine the potential of renewable energy are technology, economics, environment, and social politics, with 13 sub-criteria. Analytical hierarchy process techniques prioritize potential alternative energy sources such as wind and solar power facilities. Research findings show that environmental criteria have a higher value (0.3455) than financial criteria (0.2861), next is technological criteria (0.1734), then socio-political criteria (0.1603). Based on the results of the requirements and sub-requirements, wind power generation is the most effective and efficient alternative energy used in the Banyak Islands region (0.549), followed by solar power generation (0.451). This data shows that the area is prone to medium to high wind speeds, specifically in geographic locations facing the Indian Ocean which is located offshore.